Isoniazid-Induced Recurrent Pancreatitis - Mattioni, Sarah; Zamy, Michele; Mechai, Frederic; Raynaud, Jean-Jacques; Chabrol, Amelie; Aflalo, Vanessa; Biour, Michel; Bouchaud, Olivier (JOP. Journal of the Pancreas, 2012)
Context Drug induced pancreatitis are rare but potentially serious. Thus, drug withdrawal is warranted. Case report A 79-year-old woman who was treated with antituberculosis therapy for 5 weeks was admitted to our unit for pancreatitis. Usual etiologies of pancreatitis were eliminated. Because of vomiting, antituberculosis therapy was withdrawn and symptoms disappeared. Eight days later, the same treatment was reintroduced and the patient presented recurrent pancreatitis; thus, treatment was withheld again followed by disappearance of clinical and biological abnormalities. Two days later, a treatment without isoniazid was reintroduced and no recurrence of symptoms was observed. Conclusions We have experienced a case of isoniazid induced pancreatitis. This is a rare cause of pancreatitis but potentially fatal thus recognition of drug induced pancreatitis and definitive withdrawal of the drug is required.